2018
DOI: 10.1002/jcp.27081
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C counteracts miR‐302/367‐induced reprogramming of human breast cancer cells and restores their invasive and proliferative capacity

Abstract: Epigenetic reprogramming by embryonic stem cell-specific miR-302/367 cluster has shown some tumor suppressive effects in cancer cells of different tissues such as skin, colon, and cervix. Vitamin C has been known as a reprogramming enhancer of human and mouse somatic cells. In this study, first we aimed to investigate whether exogenous induction of miR-302/367 in breast cancer cells shows the same tumor suppressive effects previously observed in other cancer cells lines, and whether vitamin C can enhance repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
29
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 47 publications
9
29
1
Order By: Relevance
“…Therefore, suppression of BMI‐1 by miR‐16 may provide a good reason for repression of EMT in the breast cancer cells we studied. Furthermore, BMI‐1 is also repressed by miR‐302 cluster, and therefore miR‐16 may augment the suppressive impact of miR‐302 on both invasiveness and proliferative capacity of different cancer cells as we reported previously …”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Therefore, suppression of BMI‐1 by miR‐16 may provide a good reason for repression of EMT in the breast cancer cells we studied. Furthermore, BMI‐1 is also repressed by miR‐302 cluster, and therefore miR‐16 may augment the suppressive impact of miR‐302 on both invasiveness and proliferative capacity of different cancer cells as we reported previously …”
Section: Discussionsupporting
confidence: 69%
“…Previously, we demonstrated some antitumor effects of miR‐302abcd and miR‐302/367 clusters in melanoma, colon, and breast cancer cells . We showed that overexpression of miR‐302/367 cluster upregulated OCT4A , SOX2 , NANOG , LIN28A , and KLF4 expression in MDA‐MB‐231 and SK‐BR‐3 cells while MYC was downregulated . Although the transcription factors in this study did not show exactly the same expression pattern following the miR‐16 transfection, exogenous miR‐16 augmented, miR‐302/367‐induced reprogramming by upregulating OCT4A , SOX2 , NANOG , and LIN28A expression in MDA‐MB‐231 and OCT4A , NANOG , LIN28A , and KLF4 expression in SK‐BR‐3 cells.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations